Reminders and Management of Medication for Diabetes Patients Based on the Internet of Things - Binanto, Dicken Lambayu; Sulaiman; Paramitha, Nina; Fitriani, Endah (Universitas Nusa Putra, 2025)
Innovative technology solutions are developed to help patients manage their medication more effectively. Diabetes is a chronic disease that requires regular monitoring of blood sugar levels and proper regulation of medication consumption. This system is designed to assist diabetics in remembering when to take their medication and to ensure the correct dosage in accordance with the doctor’s recommendations. It utilizes an IoT device connected to a mobile application or web-based platform, allowing users to receive notifications at predetermined times. Additionally, the system includes patient condition monitoring features, such as blood sugar level tracking synchronized with measurement devices. The collected data is transmitted in real-time to the application, enabling both patients and medical personnel to monitor treatment progress and make necessary adjustments. Through the integration of IoT, this system not only enhances patient adherence to medication schedules but also provides better analysis of medication effectiveness and potential risks, thereby minimizing negligence in medication consumption. The implementation of this technology has the potential to significantly improve the quality of life for individuals with diabetes.